Removal of tetracycline from water by catalytic photodegradation combined with the microalga Scenedesmus obliquus and the responses of algal photosynthesis and transcription. (15th January 2023) - Chen, Zhehua; Ou, Dong; Gu, Gan; Gao, Shumei; Li, Xi; Hu, Changwei; Liang, Xianrui; Zhang, Yuejin
Abstract: The antibiotic tetracycline (TC) and its degradation products (TDPs) in degradation solution present serious environmental problems, such as human health damage and ecological risk; thus further treatment is required before being released into the aquatic environment. Furthermore, their environmental impact on microalgae remains unclear. In this study, TC was degraded by photocatalysis using birnessite and UV irradiation, followed by biological purification using the microalga Scenedesmus obliquus . In addition, the photosynthetic activity and transcription of the microalgae were examined to evaluate the toxicity of TC and TDPs. The results show that photocatalytic degradation efficiency reached 92.7% after 30 min, and 11 intermediate products were detected. The microalgae achieved a high TC removal efficiency (99.7%) after 8 days. Exposure to the degraded TC solution (D) resulted in significantly lower ( p  < 0.05) biomass than the pure TC (T), and S. obliquus in the T treatment showed better resilience than the D treatment. Transcriptomic assays for different treatments revealed differential gene expression mainly involving the photosynthesis, ribosome, translation and peptide metabolic progresses. The up-regulation of photosynthesis-related genes and differential expression of chloroplast genes may be important for S . obliquus to acquire high photosynthetic efficiency and growth recovery when exposed to TC and TDPs. Our study provides a reference for TC removal using a combination of catalytic degradation and microalgal purification, and it is also helpful for understanding the environmental risk of TDPs in natural aquatic environments. Highlights: Algal-based technique combined with catalysis was used for tetracycline removal. Scenedesmus obliquus exhibited excellent removal efficiency for tetracycline. Photosynthesis and transcriptomics revealed the degradation product toxicity.